Low Dose of Genistein Alleviates Mono-(2-Ethylhexyl) Phthalate-Induced Fetal Testis Disorder Based on Organ Culture Model. (28th May 2020) - Zhang, Tong-Dian; Ma, Yu-Bo; Li, He-Cheng; Chong, Tie; Wang, Zi-Ming; Zhang, Lian-Dong
Abstract : Mono-(2-ethylhexyl) phthalate (MEHP) and genistein have been classified as endocrine-disrupting chemicals (EDCs) which interfere with the differentiation and development of the male reproductive system. However, how these two EDCs would affect fetal rat testis development at a low dose was rarely studied. In this study, we established the organ culture system and applied it to evaluate testicular effects following multiple EDC exposure at a low dose. 15.5 days postcoitum fetal rat testes were dissected, cultured, and exposed to vehicle (control), GEN (1  μ mol/L, G), MEHP (1  μ mol/L, M), or GEN (1  μ mol/L)+MEHP (1  μ mol/L, G+M). Testicular cell markers, testosterone concentration, redox state, testicular histology, and testicular ultrastructure were evaluated. Our results showed that a low dose of MEHP suppressed the development of Sertoli cells, Leydig cells, and gonocytes by triggering oxidative injuries, which was consistent with the ultrastructural findings. However, coadministration of genistein at a low dose could partially attenuate MEHP-induced fetal testis damage through antioxidative action. Cotreatment of genistein at a low dose may have a promising future on its protecting role for attenuating other EDC-induced reproductive disorders during early life. Based on the results, it can be speculated that dietary intake of isoflavones may make the fetal testis less susceptible to phthalate-induced injury.